FAKTOR-FAKTOR YANG MEMPENGARUHI INDEPENDENSI AUDITOR DENGAN SIFAT MACHIAVELLIAN SEBAGAI VARIABEL MODERASI - Adeline Adeline; Dona Primasari; Sugiarto Sugiarto (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
The aim of this research is to determine the influence of audit fee and competition between public accountant office with machiavellian trait as moderating variable on auditor independence that works at Public Accounting Office in Bekasi. This research uses saturation sampling to collected 44 respondents. The collected data were analyzed using linear regression analysis and moderated regeression analysis using SPSS ver. 25. The result of this study indicate that audit fee have a negative effect on auditor independence and competition between public accounting office does not affect auditor independence. In addition, machiavellian trait moderates the effect of audit fee on auditor independence, but the trait does not moderate the effect of competition between public accounting office on auditor independence.